2010
DOI: 10.1109/tvcg.2010.164
|View full text |Cite
|
Sign up to set email alerts
|

How Information Visualization Novices Construct Visualizations

Abstract: It remains challenging for information visualization novices to rapidly construct visualizations during exploratory data analysis. We conducted an exploratory laboratory study in which information visualization novices explored fictitious sales data by communicating visualization specifications to a human mediator, who rapidly constructed the visualizations using commercial visualization software. We found that three activities were central to the iterative visualization construction process: data attribute se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
190
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(196 citation statements)
references
References 29 publications
6
190
0
Order By: Relevance
“…Our work extends the above in the following ways: Using guidelines from [12,15], we build a fully functional dashboard visualization system, and observe how novice users use the interface to create dashboards (without a human mediator [12]). We compare our observations of novices to reactions from experts, and derive additional design guidelines for visualization dashboards that target both user groups.…”
Section: Novices In Visualizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Our work extends the above in the following ways: Using guidelines from [12,15], we build a fully functional dashboard visualization system, and observe how novice users use the interface to create dashboards (without a human mediator [12]). We compare our observations of novices to reactions from experts, and derive additional design guidelines for visualization dashboards that target both user groups.…”
Section: Novices In Visualizationmentioning
confidence: 99%
“…They also suggest that visualization tools for novices should: allow user-friendly data input for common data formats; automatically provide visualizations or reasonable defaults based on data types; and use contextual information to clarify the displayed data and encoding. Grammel et al [12] investigate how novices create single charts, using a human mediator to interact with the creation interface. They found that the main activities performed by novices (apart from communicating their specifications to the mediator) are data attribute selections, visual template selections, and viewing and refinements of the above.…”
Section: Novices In Visualizationmentioning
confidence: 99%
See 3 more Smart Citations